1985
DOI: 10.1121/1.392654
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and intensity discrimination in humans and monkeys

Abstract: Frequency and intensity DLs were compared in humans and monkeys using a repeating standard "yes-no" procedure in which subjects reported frequency increments, frequency decrements, intensity increments, or intensity decrements in an ongoing train of 1.0-kHz tone bursts. There was only one experimental condition (intensity increments) in which monkey DLs (1.5-2.0 dB) overlapped those of humans (1.0-1.8 dB). For discrimination of both increments and decrements in frequency, monkey DLs (16-33 Hz) were approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
49
1
2

Year Published

1991
1991
2003
2003

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 0 publications
8
49
1
2
Order By: Relevance
“…The discrimination thresholds of our animals were within the normal range found for training primates (6,(28)(29)(30). Our animals had discrimination thresholds, (⌬F͞F), of 0.06 and 0.03.…”
Section: Discussionsupporting
confidence: 80%
“…The discrimination thresholds of our animals were within the normal range found for training primates (6,(28)(29)(30). Our animals had discrimination thresholds, (⌬F͞F), of 0.06 and 0.03.…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, if an organism's sensitivity shows signs of deteriorating with increased SL, then this may indicate that a rate code is involved. We have previously reported that monkeys exhibit qualitatively different SL functions from humans in pure tone frequency discrimination: Monkey DLs increase with increased SL, whereas human DLs decrease (Sinnott et al, 1985(Sinnott et al, , 1987a. These results are also consistent with a hypothesis that monkeys use a rate code that breaks down due to rate saturation as SL increases.…”
supporting
confidence: 92%
“…For birds and monkeys, however, this ratio appeared much smaller. Animals appeared sensitive to formant changes of less than 125 Hz in vowels, yet their pure tone DLs are as high as 15-20 Hz at 1.0 kHz (Sinnott et al, 1980(Sinnott et al, , 1985. Thus animal formant DLs appear to be only about five or six times larger than their pure tone frequency DLs.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The auditory thresholds were slightly lower than those determined with a similar method in Old World monkeys, using a 2-kHz standard (Sinnott, Owren, & Petersen, 1987) or a I-kHz standard (Sinnott, Petersen, & Hopp, 1985). They were also in agreement with those derived in human infants, but they were higher than those derived in human adults (Sinnott & Aslin, 1985;Wier, Jesteadt, & Green, 1977).…”
Section: Comparison To Other Paradigmssupporting
confidence: 74%